Strategi Mitigasi Bencana Longsor untuk Meningkatkan Ketahanan Masyarakat di Desa Ngargosari Kecamatan Loano Kabupaten Purworejo - Zaida Muflih, Ghufron; Barokah, Umi; Zuhdi, Rasyid; Fathani, Teuku Faisal; Wilopo, Wahyu (Universitas Gadjah Mada, 2025)
ABSTRACT Disasters are events that threaten people's lives and can cause loss of life, property, as well as environmental and psychological impacts. Landslides, as one of the natural disasters, occur due to slope instability triggered by geological and hydrological factors. Ngargosari Village, Kecamatan Loano, Purworejo Regency, has a geographical condition of steep hills with an altitude of ±450 meters above sea level which makes it prone to landslides. This research aims to increase community resilience to landslides through a community-based mitigation approach and appropriate technology in the KOSABANGSA program. The method used includes preparation, implementation, and evaluation stages. Mitigation activities include socialization, geological survey, vulnerability mapping, installation of early warning system (EWS), evacuation signs, preparation of evacuation fixed procedures, and implementation of evacuation simulation. Evaluation results show an increase in physical resilience through the availability of evacuation routes and EWS that function in real-time. The community's capacity resilience also increased, as shown by the average score of disaster understanding at 78% and infrastructure understanding at 86%. EWS implementation and participatory education proved effective in improving community preparedness. A collaborative approach between academics, village government, and residents is a key factor in building a resilient and sustainable mitigation system